A Twisted Wire‐Shaped Dual‐Function Energy Device for Photoelectric Conversion and Electrochemical Storage1. (16th April 2014) - Sun, Hao; You, Xiao; Deng, Jue; Chen, Xuli; Yang, Zhibin; Chen, Peining; Fang, Xin; Peng, Huisheng
Abstract A wire‐shaped energy device that can perform photoelectric conversion and electrochemical storage was developed through a simple but effective twisting process. The energy wire exhibited a high energy conversion efficiency of 6.58 % and specific capacitance of 85.03 μF cm−1 or 2.13 mF cm−2, and the two functions were alternately realized without sacrificing either performance.